Imperial oil: the anatomy of a Nigerian oil insurgency - Watts, Michael (ERDKUNDE, 2008)
Alternative non-Persian Gulf sources of oil-supply are central to American geostrategic interests in the period since 2001. Vice President Cheney’s National Energy Strategy Report in 2001 bemoaned a dependency on foreign powers that “do not have America’s interests at heart”. Africa has emerged as one of the major new sources of US oil and gas supply. If Africa is not as well endowed in hydrocarbons (both oil and gas) as the Persian Gulf states, the West African Gulf of Guinea has nonetheless become the subject of fierce competition by energy companies over the continent’s copious reserves of natural gas and its sweet light oil. IHS Energy – one of the oil industry’s major consulting companies – expects African oil production, especially along the Atlantic littoral, to attract huge exploration investment contributing over 30% of world liquid hydrocarbon production by 2010. Over the last five years when new oil-field discoveries were a scarce commodity, Africa contributed one in every four barrels of new petroleum discovered outside of Northern America. This article addresses the new scramble for Africa in the context of a new conjuncture of global forces: military neoliberalism and the Global War on Terror (GWOT). I lay out the broad landscape of oil production on the continent and the extent to which, in the wake of a catastrophic two decades of neoliberal structural adjustment, investment in oil and gas dominates direct foreign investment in Africa. I then turn to the specific case of Nigeria – the most important producer of oil and gas on the continent and the petro-state of most geostrategic concern to the US – and use it as an exemplar of the failure of oil-based development. Central to this analysis is the emergence of new forms of armed insurgency in the oil producing Niger Delta that has rendered the entire area virtually ungovernable, increasingly so since the emergence in late 2005 of a new armed group MEND (the Movement for the Emancipation of the Nigeria Delta). I conclude with an account of the dynamics of this ungovernability – a pattern replicated throughout the Gulf of Guinea – and how this instability feeds into an American imperial vision to militarize the region.